Participation of women in development projects in the SADC region : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Olifant, Sisimogang Pinkie M (Massey University, 1996)
The key to the empowerment of women is their participation at all the stages and all levels of the development project cycle. This thesis examines participation of women in development projects in the Southern African Development Community region. Its main objective is to analyse evaluations of New Zealand's Voluntary Agency Support Scheme funded projects in Africa between 1988 and 1991. There was unequal gender participation in all the projects. Despite lack of empowerment of women in the projects, important development needs of women were met. This could be linked to the nature of traditional societies in this region. The recommendations focus on the need for equal participation of women and men in development projects at the planning, implementation, monitoring and evaluation stages as well as equal distribution of project benefits. Furthermore, attention is focused on World Bank and International Monetary Fund Structural Adjustment Programmes, the debt crisis, Southern and Northern NGO partnerships and the adoption of analytical framework to analyse projects.
Keywords: Southern African Development Community; Women in development; Women in agriculture; Africa, Southern